RESPONSABILIDADE SOCIAL E CIDADANIA EMPRESARIAL FACE À SEGURANÇA DO TRABALHO - Eckhardt, Moacir; Ribeiro, Luís F. M.; Sackser, Gilberto; Duarte, Luiz C. d. S.; Ferreira, Thiago A.; Benini, Lucas (Salão do Conhecimento, 2013)
Resumo